Projeto de requalificação da Rua Socialismo e criação de espaços públicos em lotes ociosos - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2018)
The quality of public spaces in a neighborhood is reflected in the quality of life of the people who live in or through it. The human scale in urban projects is one of the factors pointed out by some authors as essential for the vitality of these spaces. The objective of this study is to verify the influence that public spaces exert on people's quality of life, to analyze their currently conditions in the Renascer I neighborhood in Macapá-AP, and to propose improvements for them. The methodology used was the research of documents in municipal and state agencies, consultation of bibliography concerning the subject, field surveys and observation of the study area, and interviews with residents. As a result, in view of the importance of the main street of the neighborhood, Socialismo Street, for the dynamics of this, a project of urban requalification was developed for this route and for idle lots bordering it.
Keywords: Espaços públicos; Requalificação urbana; Planejamento urbano; Qualidade de vida; CNPQ::CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO